Resistance to flow in sand channels - Richardson, E. V. (Everett V.), author; Colorado State University, publisher (Colorado State University. Libraries, 1965)
A theoretical and laboratory investigation was made of resistance to flow in sand-bed channels. The objectives were to determine the type of flow and energy dissipation in sand-bed channels and develop equations and relations for predicting resistance to flow and mean velocity. The types of flow, energy dissipation and, thus resistance to flow in sand-bed channels is extremely variable because (1) the configuration of the boundary, (2) the properties of the fluid, and (3) the characteristics of the turbulence are functions of the flow, fluid, and sand characteristics and of the geometry of the channel. The boundary configurations that form in a sand bed are ripples, ripples on dunes, dunes, plane bed, antidunes or chutes-and-pools. The type of flow in a sand channel with constant discharge and average energy gradient may be steady or unsteady and uniform or nonuniform, depending on the boundary configuration. With the array of boundary configurations found in sand channels, the dissipation of energy may result from grain roughness, form roughness, acceleration of the flow, breaking waves or any combinations of them. With variable boundary configuration, type of flow and energy dissipation, it is impossible to determine a general equation to predict resistance to flow and mean velocity for all flow conditions. However, if the boundary configuration is known, specific relations and equations are developed for predicting resistance to flow. For steady uniform flow, the equations are based on integrating the Reynolds equation for turbulent flow. The coefficients in the integrated equation were determined from a study of the velocity distribution and verified using the mean flow variables. For nonuniform and (or) unsteady flow, resistance to flow is determined by applying a correction term to the equation developed for flow over a plane bed. The correction term compensates for the increase in energy dissipation resulting from form roughness, flow acceleration and breaking waves. The study of the velocity profiles for plane bed flow when there is considerable bed-material movement, determined that there is an inner and outer flow zone. In the inner zone, the slope A and intercept B in the relation u = A ln y + B are variable. The variation of the slope and intercept are functions of the size and concentration of suspended sediment in the inner zone. In the outer zone , the slope and intercept are constant.
CER65EVR27.
June, 1965.
In partial fulfillment of the requirements for the Degree of Doctor of Philosophy in Civil Engineering.
Keywords: Channels (Hydraulic engineering); Hydraulics